Robust Control of Doubly Fed Induction Generator Using Fractional Order Control - Abdelaziz Azza; Hamid Kherfane (Institute of Advanced Engineering and Science, 2018)
In this paper, we present a robust control of a variable speed Doubly Fed Induction Generator (DFIG)-based Wind Energy Conversion System (WECS), using Fractional Order Control (FOC) to prevent system deterioration under different critical conditions (external disturbance, measurement noise and DFIG parameters variation). In order to extract the maximum power from the wind, a Maximum Power Point Tracking (MPPT) strategy based on rotor speed control is proposed. Furthermore, a vector control strategy is used for controlling active and reactive powers of DFIG. Additionally, a simple design method of Fractional Order Proportional Integral (FOPI) controller is proposed. Finally, the system’s performance is tested and compared according to reference tracking, robustness, disturbance rejection and noise minimization.